Cardiovascular disease and depression: a bidirectional relationship and its clinical implications - Wu, Jianbo; Tian, Zifan; Qi, Zhimin; Liu, Xiaoqun; Yu, Peng (Frontiers in Psychiatry, 2026)
There is strong evidence that depression is linked to greater rates of morbidity and death in people with cardiovascular disease (CVD), supporting its status as a key risk factor for the condition. Recent researches suggest a reciprocal relationship, with CVD potentially predisposing people to depressive disorders. Notably, depression has a high comorbidity rate with major cardiovascular disorders such as coronary artery disease and myocardial infarction, which may have a severe impact on patients’ long-term outcomes. Several pathways, including neuroendocrine dysregulation, activation of the inflammatory system, and behavioral alterations, appear to underlie the connection between depression and CVD. On the other hand, CVD may lead to the pathophysiology of depression by altering brain hemodynamics and causing blood–brain barrier (BBB) damage. Current therapeutic approaches stress a multimodal approach that combines drug interventions, cognitive behavioral therapy, and lifestyle changes to improve patient results. This review summarizes the latest research findings on the complex connection between depression and cardiovascular diseases, as well as contemporary treatment options and clinical consequences.